2022
DOI: 10.1038/s41598-022-13367-y
|View full text |Cite
|
Sign up to set email alerts
|

On the suitability of phillipsite-chabazite zeolitite rock for ammonia uptake in water: a case study from the Pescara River (Italy)

Abstract: Ionic exchange tests have been performed on superficial wastewaters to remove ammonia using a volcanic zeolitized rock from Lazio Region (Central Italy). The zeolitite (natural zeolite) is characterized by chabazite, phillipsite and minor amounts of sanidine, leucite and analcime. After preliminary column experiments in laboratory focused to determine the saturation time of the zeolitite, a pilot plant was built up on a little water course near the area of San Giustino channel (Abruzzo Region, Central Italy). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Phillipsite belongs to the PHI type (crystal chemical data |K2 (Ca, Na2)2 (H2O)12| [Al6Si10O32]-PHI, [4] and is structurally built up by layers of four-and eight-member rings forming double crankshaft chains, the framework contains three The field of application of phillipsite is not as wide as that of clinoptilolite, but phillipsite was used for ammonia adsorption [5], in removal of heavy metals [6] and other contaminants [7,8] from waste waters, and interest in faujasite-phillipsite and phillipsitechabazite rocks has recently increased [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Phillipsite belongs to the PHI type (crystal chemical data |K2 (Ca, Na2)2 (H2O)12| [Al6Si10O32]-PHI, [4] and is structurally built up by layers of four-and eight-member rings forming double crankshaft chains, the framework contains three The field of application of phillipsite is not as wide as that of clinoptilolite, but phillipsite was used for ammonia adsorption [5], in removal of heavy metals [6] and other contaminants [7,8] from waste waters, and interest in faujasite-phillipsite and phillipsitechabazite rocks has recently increased [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Zeolite has been used as an ion exchanger to absorb ammonium [14]. It was extensively tested in agriculture [15][16][17][18], freshwater basins [19], sewage effluent treatment for the reduction of ammonia and heavy metals [20][21][22][23], and more recently in the breeding of seabass juveniles [24]. In a seawater experiment, Lopez-Ruiz and Goméz-Garrudo [25] showed that more zeolite must be used to achieve the same amount of ammonium subtraction as obtained in freshwater experiences.…”
Section: Introductionmentioning
confidence: 99%